Comparative Study between Caspar Cervical Retractor System and Traditional S Retractor in Application on Anterior Cervical Decompression and Fixation. Issue 2 (13th December 2022) - Wang, Lianlei; Qiu, Cheng; Tian, Yonghao; Su, Junxiao; Li, Hao; Ma, Zhihao; Yuan, Suomao; Liu, Xinyu
Abstract : Objective: Although Caspar cervical retractor system (CCRS) is commonly utilized in anterior cervical decompression and fixation (ACDF), most urban hospitals still use both traditional S retractor and CCRS in conventional anterior cervical surgeries. Related data to evaluate the effect are required to be reported. The aim of this study is to compare the efficacy between using the traditional cervical S retractor and CCRS in anterior cervical decompression and fixation ACDF. Methods: The retrospective study that total 360 patients received ACDF using different retractors (traditional S retractor or CCRS) were enrolled in this study from January 2010 to January 2020. Width change rate of cervical prevertebral soft tissue, throat symptoms, and subjective experiences of the operating surgeons were evaluated by t ‐test or analysis of variance (ANOVA) respectively. Results: The width change rate of prevertebral soft tissue was significantly higher in the S retractor group than that of the CCRS group both in single segment group (40.9% vs 20.8%, P  < 0.05) and double segments group (45.8% vs 25.2%; p  < 0.05). In the three segments group, the width change rate of prevertebral soft tissue was higher in the S retractor group than that of the CCRS group, but with no statistical significance (27.3% vs 23.6%; P  > 0.05). The incidence rates of dysphagia, dyspnea, and throat discomfort in the traditional S retractor group were significantly higher compared to the CCRS group ( P  < 0.05), while satisfactory rate of surgeon was higher in the CCRS group ( P  < 0.05). However, there was no correlation between anterior soft tissue rate and operative time ( P  > 0.05), as well as the width change rate of anterior soft tissue and the DNRS score ( P  > 0.05). Conclusion: CCRS was superior compared to the traditional S retractor in reducing the postoperative complications and the postoperative fatigue of surgeon. Meanwhile, the width change rate of prevertebral soft tissue was not related to operative time and DNRS score. Abstract : The application of two retractors in operation.